Effects of conjugated estrogen and bazedoxifene on hemostasis and thrombosis in mice. Issue 6 (June 2019) - Noirrit, Emmanuelle; Buscato, Mélissa; Dupuis, Marion; Payrastre, Bernard; Fontaine, Coralie; Arnal, Jean-François; Valera, Marie-Cécile
Abstract : Estrogen–progestin therapy was previously considered as the standard of care for managing bothersome symptoms associated with menopause, but it increases risks of breast cancer and of thromboembolism. The combination of conjugated estrogen (CE) with bazedoxifene (BZA) named tissue-selective estrogen complex (TSEC) was designed to minimize or even abrogate the undesirable effects on breast, while maintaining the beneficial effects such as prevention of osteoporosis and suppression of climacteric symptoms. The risk on thromboembolism associated with TSEC is unknown, although the clinical available data are reassuring. The aim of this study was to define the impact of a chronic administration of CE, BZA or CE + BZA on hemostasis and thrombosis in ovariectomized mice. As expected, CE, but not BZA neither CE + BZA, induced uterine and vagina hypertrophy. As previously demonstrated for 17β-estradiol (E2), we found that CE (i) increased tail-bleeding time, (ii) prevented occlusive thrombus formation in injured carotid artery and (iii) protected against collagen/epinephrine-induced thromboembolism. Thus, whereas BZA antagonized CE action on reproductive tissues, it had no impact on the effect of CE on hemostasis, thromboembolism and arterial thrombosis in mice. CE + BZA shared the anti-thrombotic actions of CE in these mouse models. If a similar process is at work in women, CE combined with BZA could contribute to minimize the risk of thrombosis associated with hormone replacement therapy.